Comprehensive evaluation of genetic variants using chromosomal microarray analysis and exome sequencing in fetuses with congenital heart defect. (1st September 2021) - Qiao, F.; Wang, Y.; Zhang, C.; Zhou, R.; Wu, Y.; Wang, C.; Meng, L.; Mao, P.; Cheng, Q.; Luo, C.; Hu, P.; Xu, Z.
ABSTRACT: Objective: To evaluate comprehensively, using chromosomal microarray analysis (CMA) and exome sequencing (ES), the prevalence of chromosomal abnormalities and sequence variants in unselected fetuses with congenital heart defect (CHD) and to evaluate the potential diagnostic yields of CMA and ES for different CHD subgroups. Methods: This was a study of 360 unselected singleton fetuses with CHD detected by echocardiography, referred to our department for genetic testing between February 2018 and December 2019. We performed CMA, as a routine test for aneuploidy and copy number variations (CNV), and then, in cases without aneuploidy or pathogenic CNV on CMA, we performed ES. Results: Overall, positive genetic diagnoses were made in 84 (23.3%) fetuses: chromosomal abnormalities were detected by CMA in 60 (16.7%) and sequence variants were detected by ES in a further 24 (6.7%) cases. The detection rate of pathogenic and likely pathogenic genetic variants in fetuses with non‐isolated CHD (32/83, 38.6%) was significantly higher than that in fetuses with isolated CHD (52/277, 18.8%) ( P  < 0.001), this difference being due mainly to the difference in frequency of aneuploidy between the two groups. The prevalence of a genetic defect was highest in fetuses with an atrioventricular septal defect (36.8%), ventricular septal defect with or without atrial septal defect (28.4%), conotruncal defect (22.2%) or right ventricular outflow tract obstruction (20.0%). We also identified two novel missense mutations (c.2447G>C, p.Arg816Pro; c.1171C>T, p.Arg391Cys) and a new phenotype caused by variants in PLD1 . Conclusions: Chromosomal abnormalities were identified in 16.7% and sequence variants in a further 6.7% of fetuses with CHD. ES should be offered to all pregnant women with a CHD fetus without chromosomal abnormality or pathogenic CNV identified by CMA, regardless of whether the CHD is isolated. © 2020 International Society of Ultrasound in Obstetrics and Gynecology Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Objetivo: Evaluar de forma exhaustiva, mediante el análisis de microarrays cromosómicos (AMC) y la secuenciación del exoma (SE), la prevalencia de anomalías cromosómicas y variantes de secuencia en fetos no seleccionados con cardiopatía congénita (CC) y evaluar los posibles rendimientos del diagnóstico de AMC y SE para diferentes subgrupos de CC. Métodos: Se trata de un estudio de 360 embarazos con feto únicos no seleccionados con CC detectada por ecocardiografía, remitidos a nuestro departamento para la realización de pruebas genéticas entre febrero de 2018 y diciembre de 2019. Como prueba de rutina para la aneuploidía y las variantes del número de copias (VNC) se realizó un AMC, y luego, en los casos sin aneuploidía o VNC patógenas en el AMC, se realizó una SE. Resultados: En general, se realizaron diagnósticos genéticos positivos en 84 (23, 3%) fetos: se detectaron anomalías cromosómicas mediante AMC en 60 (16, 7%) y variantes de secuencia mediante SE en otros 24 (6, 7%) casos. La tasa de detección de variantes genéticas patógenas y probablemente patógenas en los fetos con CC no aislada (32/83, 38, 6%) fue significativamente mayor que en los fetos con CC aislada (52/277, 18, 8%) (P<0, 001), siendo esta diferencia debida principalmente a la diferencia en la frecuencia de aneuploidía entre los dos grupos. La prevalencia de un defecto genético fue más alta en los fetos con comunicación auriculoventricular (36, 8%), comunicación interventricular con o sin defecto septal auricular (28, 4%), defecto conotruncal (22, 2%) u obstrucción del tracto de salida del ventrículo derecho (20, 0%). También se identificaron dos nuevas mutaciones de aminoácidos de sentido alterado (c.2447G>C, p.Arg816Pro; c.1171C>T, p.Arg391Cys) y un nuevo fenotipo causado por variantes en PLD1. Conclusiones: Se identificaron anomalías cromosómicas en el 16, 7% de los fetos con CC y variantes de secuencia en otro 6, 7%. La SE debe ofrecerse a todas las mujeres embarazadas con un feto con CC sin anomalía cromosómica o VNC patógena identificada mediante AMC, independientemente de que la CC sea aislada. 摘要: 目的: 采用染色体微阵列分析(CMA)和外显子组测序(ES)，综合评估未经选择的先天性心脏畸形胎儿中染色体异常的患病率及序列变异，并评估在不同的先天性心脏病(CHD)亚组中CMA和ES的潜在诊断率。 方法: 这是一项针对360名未经选择的(经超声心动图检测到的)CHD单胎的研究，于2018年2月至2019年12月之间转介至我科室进行基因检测。我们进行了CMA，作为异倍体和拷贝数变异(CNV)的一项常规检测，然后，又对CMA后无异倍体或致病CNV的病例进行了ES。 结果: 总的说来，对84个胎儿(23.3%)做出了确定的基因诊断:用CMA检测到60个存在染色体异常的胎儿(16.7%)，而且用ES在另外24个胎儿(6.7%)中又检测到序列变异。致病性和可能致病基因变异在非单纯性CHD胎儿中的检出率(32/83，38.6%)明显高于其在单纯性CHD胎儿中的检出率(52/277, 18.8%)(P<0.001)，这一差异主要是由于两组之间非整倍体率的不同造成的。基因缺陷患病率最高的胎儿有房室间隔缺损(36.8%)、室中隔缺损(不论是否存在心房间隔缺损)(28.4%)、圆锥动脉干畸形(22.2%)或右心室出口阻塞(20.0%)。我们还识别出两个新型错义突变(c.2447G>C、p.Arg816Pro；c.1171C>T、p.Arg391Cys)和一个因PLD1中变异所致的新表型。 结论: 在CHD胎儿中识别出16.7%有染色体异常和另外6.7%有序列变异。应当对怀有CHD胎儿(经CMA无染色体异常或致病CNV)的所有孕妇进行ES，不管胎儿的CHD是否为单纯性。 © 2020年国际妇产科超声学会。